2000
DOI: 10.4049/jimmunol.164.2.589
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 gp120 Induces IL-4 and IL-13 Release from Human FcεRI+ Cells Through Interaction with the VH3 Region of IgE

Abstract: HIV-1 glycoprotein (gp) 120 from different clades is a potent stimulus for IL-4 and IL-13 release from basophils purified from healthy individuals seronegative for Abs to HIV-1 and HIV-2. IL-4 mRNA, constitutively present in basophils, was increased after stimulation by gp120 and was inhibited cyclosporin A and tacrolimus. IL-4 and IL-13 secretion from basophils activated by gp120 was not correlated. There was a correlation between the maximum gp120- and anti-IgE-induced IL-4 release from basophils. The averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
135
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(140 citation statements)
references
References 67 publications
3
135
0
Order By: Relevance
“…Second, the chemotactic activity of Tat on human Fc⑀RI ϩ cells might contribute to increase the local density of mast cells and basophils available for HIV-1 interaction through the virus bound or shed gp120. In fact, we have recently demonstrated that gp120 from different clades interacts with the V H 3 region of IgE present on human Fc⑀RI ϩ (35). Third, the superantigenic interaction between gp120 and IgE leads to the rapid synthesis and release of IL-4 and IL-13 from human Fc⑀RI ϩ cells (35).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, the chemotactic activity of Tat on human Fc⑀RI ϩ cells might contribute to increase the local density of mast cells and basophils available for HIV-1 interaction through the virus bound or shed gp120. In fact, we have recently demonstrated that gp120 from different clades interacts with the V H 3 region of IgE present on human Fc⑀RI ϩ (35). Third, the superantigenic interaction between gp120 and IgE leads to the rapid synthesis and release of IL-4 and IL-13 from human Fc⑀RI ϩ cells (35).…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that the interaction between a gp120 binding site and the V H 3 domain of IgE on human basophils and mast cells induces the release of Th2 cytokines (IL-4 and IL-13) from human Fc⑀RI ϩ cells without synthesizing Th1-type cytokines (e.g., IFN-␥) (35). The presence of CCR3 receptors on the majority of basophils (39,40) and on a significant percentage of human mast cells (38,40) and their role as coreceptor for HIV-1 infection (7)(8)(9)(10) suggest that the interplay between Tat protein, which upregulates CCR3 receptors, and Fc⑀RI ϩ cells could facilitate HIV infection of these cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Basophil activation by IPSE/␣-1 was found to depend on the presence of IgE on the surface of the basophils irrespective of IgE's antigen specificity (7,12). IgE-dependent, antigen-independent basophil activation is well known from multivalent lectins or B cell superantigens, which cross-link IgE via binding to its carbohydrate side chains or directly to its immunoglobulin backbone, respectively (13,14). However, molecular details of the mechanism of action of IPSE/␣-1 are not yet known.…”
mentioning
confidence: 99%